2008
DOI: 10.1111/j.1539-6975.2008.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Income Drawdown Schemes for a Defined‐Contribution Pension Plan

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent AbstractIn retirement a pensioner must often decide how much money to withdraw from a pension fund, how to invest the remaining funds, and whether to purchase an annuity. These decisions are addressed here by introducing a number of income drawdown schemes, which are relevant to a defined-contribution personal pension plan. The optimal asset allocation is defined so that it minimise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…However, rather than specify a target fund, they consider a benchmark and measure the performance of the pension fund against this benchmark. In contrast to Gerrard et al (2006), Emms and Haberman (2008) minimize the loss of the pension fund relative to the benchmark; there is no penalty if the pension fund outperforms the benchmark. For their model the income drawdown strategy is prescribed: it is defined so that the fund performance is driftless under the optimal stock allocation strategy.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…However, rather than specify a target fund, they consider a benchmark and measure the performance of the pension fund against this benchmark. In contrast to Gerrard et al (2006), Emms and Haberman (2008) minimize the loss of the pension fund relative to the benchmark; there is no penalty if the pension fund outperforms the benchmark. For their model the income drawdown strategy is prescribed: it is defined so that the fund performance is driftless under the optimal stock allocation strategy.…”
Section: Introductionmentioning
confidence: 93%
“…Other targets lead to different forms of dynamic strategy, as we shall see in the next section. Emms and Haberman (2008) define fair-value income drawdown such that under an optimal stock allocation the fund performance is a martingale. For an LQ optimization problem, a similar idea is to require that the expected fund size is a fixed percentage below the target for the duration of the drawdown period.…”
Section: Figure 1 Endogenous Fund Targets (A) and Drawdown Targets (Bmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Haberman and Sung [2] try to minimize the 'solvency' and 'contribution rate' risks in order to stabilize the pension fund, and Cairns et al try to optimize the terminal utility gained from the pension fund with a stochastic interest rate [3]. Some other examples of the studies that deal with the optimal asset allocations for pension funds can be found in [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. On the other hand, there are limited numbers of studies that consider a target or a guaranteed wealth concept.…”
Section: Introductionmentioning
confidence: 99%